Non-standard employment, low standard of living? The role of labour market and social policy measures in preventing material deprivation in different employment trajectories in Europe - Fridolin Wolf (International Journal of Social Welfare, 2024)
Abstract While the poverty risks of non-standard employment have been explored extensively, this study focuses on the role of activation-oriented social policy in alleviating material deprivation for persons with non-standard employment histories. Using EU-SILC data, individuals over a four-year period were analysed. I focused on substantial earners and distinguished between six non-standard employment histories expected to benefit from activation measures. Multi-level models revealed that compared to standard employment histories, all non-standard employment histories had higher material deprivation risks but to substantially different extents. At the macro level, participation in activation measures, expenditures in formal childcare and minimum income protection reduced material deprivation. Participation in training can be interpreted as an equaliser, as the deprivation gap between standard and most non-standard employment history types diminished. As expenditure- and participation-based measures differed significantly, evaluating the success of activation strategies in reducing inequalities and alleviating poverty highly depends on the measurement of activation.
Keywords: 330; activation; atypical employment; employment history; European social policy; material deprivation; minimum income protection; non-standard employment; social investment